Thermal processing of a degradable carboxylic acid‐functionalized polycarbonate into scaffolds for tissue engineering. Issue 7 (22nd May 2021) - Murthy, N. Sanjeeva; Shultz, Robert B.; Iovine, Carmine P.; Kohn, Joachim
Abstract: Degradable polymers are often desirable for the fabrication of medical implants, but thermal processing of these polymers is a challenge. We describe here how these problems can be addressed by discussing the extrusion of fibers and injection molding of bone pins from a hydrolytically degradable tyrosine‐derived polycarbonate. Our initial attempts produced fibers and pins with bubbles, voids, and discoloration and resulted in the formation of large polymer plugs that seized screws and blocked extruder dies. The material and process parameters that contribute to these issues were investigated by studying the physical and chemical changes that occur during processing. Differential scanning calorimetry and thermogravimetric analysis combined with IR analysis showed that residual moisture and solvents in conjunction with heat cause degradation and crosslinking as indicated by gel permeation chromatography. Rheology and melt flow index measurements were useful in characterizing the extent of dependence of polymer viscosity on temperature and molecular weight. With these insights, we could process our polymer into fibers and rods by controlling residual moisture, time, and temperature and by adjusting processing parameters in real time. The systematic approach described here is applicable to other degradable polymers that are difficult to process. Abstract : Challenges in thermal processing of degradable polymers can be met by understanding the mechanisms of degradation‐induced changes in the polymer. Detailed characterization of the degradation products will lead to a selection of processing parameters for successful extrusion, thermoforming, and injection molding of the desired products.